Genomic differentiation and patterns of gene flow between two long‐tailed tit species (Aegithalos). Issue 23 (8th November 2017) - Zhang, Dezhi; Song, Gang; Gao, Bin; Cheng, Yalin; Qu, Yanhua; Wu, Shaoyuan; Shao, Shimiao; Wu, Yongjie; Alström, Per; Lei, Fumin
Abstract: Patterns of heterogeneous genomic differentiation have been well documented between closely related species, with some highly differentiated genomic regions ("genomic differentiation islands") spread throughout the genome. Differential levels of gene flow are proposed to account for this pattern, as genomic differentiation islands are suggested to be resistant to gene flow. Recent studies have also suggested that genomic differentiation islands could be explained by linked selection acting on genomic regions with low recombination rates. Here, we investigate genomic differentiation and gene‐flow patterns for autosomes using RAD‐seq data between two closely related species of long‐tailed tits ( Aegithalos bonvaloti and A. fuliginosus ) in both allopatric and contact zone populations. The results confirm recent or ongoing gene flow between these two species. However, there is little evidence that the genomic regions that were found to be highly differentiated between the contact zone populations are resistant to gene flow, suggesting that differential levels of gene flow is not the cause of the heterogeneous genomic differentiation. Linked selection may be the cause of genomic differentiation islands between the allopatric populations with no or very limited gene flow, but this could not account for the heterogeneous genomic differentiation between the contact zone populations, which show evidence of recent or ongoing gene flow.